Maine America's coast - Perkins, Jack, 1933-; International Video Network (Ramon, Calif. : International Video Network, 1995)
A beautiful tour of the Maine coastline exploring its length, seeing its sights, and sharing its lives.
VHS format.
Keywords: Maine -- Description and travel